Prognostic and therapeutic importance of lymphadenectomy in gynecological cancers - Ayhan, A; Çelik, H; Dursun, P; Gultekin, M; Yuce, K (I R O G Canada, Inc, 2004)
Lymphadenectomy has been a matter of interest for years because of the increased morbidity rates in gynecological cancers due to the procedure itself and because the procedure requires experience. Although a number of alternative methods have been developed to find out the prevalence of gynecological cancers, dissection and histopathological evaluation of lymph nodes is still the gold standard in detecting disease. Even though there are opposing views regarding this approach, since the morbidity rate has decreased over the years many studies in the literature report that lymphadenectomy has prognostic and therapeutic value. Its contribution to survival can be attributed both to its being determinant in postoperative treatment modifications and to debulking and lymphadenectomy itself. In order to reap the prognostic and therapeutic benefit expected from lymphadenectomy, a sufficient number of lymph nodes must be dissected. Surgical experience is important both for the procedure itself and to reduce the morbidity due to the procedure. This study discusses the prognostic and therapeutic importance of lymphadenectomy in ovarian, endometrial, cervical and vulvar cancers.
Keywords: lymphadenectomy; prognostic; therapeutic; ovarian cancer; endometrial cancer; cervical cancer; vulvar cancer